De dependencia e insolvencia: el Banco de Oaxaca, 1902-1909 - Gamboa Ojeda, Leticia (El Colegio de México, A.C., 2006)
Although the small Bank of Oaxaca was created in 1902, it was conceived of a year before, as a branch  of the Eastern  Bank of Mexico (Banco Oriental de México), property of Spanish capitalists in Puebla with backgrounds, interests and relatives in Oaxaca, whom they invited to participate in their project. This work studies how the Bank of Oaxaca depended on the Eastern Bank during its brief existence (1902-1909), with special focus on the irregular and risky ways in which it operated,  based on a simulation  strategy: abiding the law, but actually breaking it; having a social capital that soon ceased to exist; enjoying liquidity in times of insolvency; and “merging” with the Banco Oriental instead of being incorporated. This strategy was implemented in the last period of the Bank of Oaxaca in order to disguise as success the failure produced by its corrupt operation.